Knowledge and Attitude toward Bariatric Surgery among Family Physicians in Cluster 2, Riyadh City, Saudi Arabia - Alwhibi, Mohammed W.; Alfawaz, Abdulrahman M.; Alfakhri, Mohannad M.; Alsadhan, Khalid F. (International Journal of Innovative Research in Medical Science, 2022)
Aim: The present study aimed at investigating knowledge and attitudes towards bariatric surgery among family medicine physicians at cluster two in Riyadh city. Method: A cross-sectional study using a self-filled questionnaire was performed during the period between October and November 2021 over a study sample of 223 family medicine physicians from cluster two health care facilities in Riyadh city; namely King Fahad Medical City, Prince Mohammad Bin Abdul Aziz Hospital and the primary care centers. Data were analyzed using the SPSS software through descriptive statics and Chi-square analysis. Results: The findings of the study showed that 67.6% (n=151) were able to identify cases that should be considered for bariatric surgery, 81.6% (n=182) identified the safest way to perform weight loss surgery (laparoscopic), 87.9% (n=196) identified the research-based evidenced outcome of surgical management of obesity (extending life expectancy with increase in quality of life) compared to conservative treatment, and 87% (n=184) identified cases that should be referred to bariatric surgery based on their body mass index (BMI) range. In addition, the findings of the study showed that family medicine physicians had positive attitudes toward bariatric surgery in term of its effectiveness and outcomes. Finally, the study found significant statistical differences in the knowledge score based on physicians’ years of practice (Χ2=40.9278, p≤0.05). Conclusion: The study concluded that the family medicine physicians at cluster two in Riyadh city had varied level of knowledge and positive attitudes regarding bariatric surgery. The study recommended increasing family medicine physicians’ knowledge and awareness regarding the benefits, consequences, techniques and rationale of bariatric surgery through engaging them in basic and advanced health education workshops and courses concerned with surgical management of obesity and metabolic disorders.